Caregiver socioemotional health as a determinant of child well‐being in school‐aged and adolescent Ugandan children with and without perinatal HIV exposure. Issue 5 (13th March 2019) - Webster, Kyle D.; de Bruyn, Miko M.; Zalwango, Sarah K.; Sikorskii, Alla; Barkin, Jennifer L.; Familiar‐Lopez, Itziar; Musoke, Philippa; Giordani, Bruno; Boivin, Michael J.; Ezeamama, Amara E.
Abstract: Objective: Caregiver socio‐emotional attributes are major determinants of child well‐being. This investigation in vulnerable school‐aged Ugandan children estimates relationships between children's well‐being and their caregiver's anxiety, depression and social support. Methods: Perinatally HIV‐infected, HIV‐exposed uninfected and HIV‐unexposed Ugandan children and their caregivers were enrolled. Perinatal HIV status was determined by 18 months of age using DNA‐polymerase chain‐reaction test; status was confirmed via HIV rapid diagnostic test when children were 6–18 years old. Five indicators of child well‐being (distress, hopelessness, positive future orientation, esteem and quality of life (QOL)) and caregivers' socioemotional status (depressive symptoms, anxiety and social support) were measured using validated, culturally adapted and translated instruments. Categories based on tertiles of each caregiver psychosocial indicator were defined. Linear regression analyses estimated percent differences ( β ) and corresponding 95% confidence intervals (CI) for child well‐being in relation to caregiver's psychosocial status. Results: As per tertile increment, caregiver anxiety was associated with 2.7% higher distress (95%CI:0.2%, 5.3%) and lower self‐esteem/QOL ( β  = −1.3%/−2.6%; 95%CI: −5.0%, ‐0.2%) in their children. Child distress/hopelessness increased ( β  = 3.3%/7.6%; 95%CI:0.4%, 14.7%) and self‐esteem/QOL decreased 2.3% ( β  = −2.3%/−4.4%; 95%CI: −7.2%, −1.3%) as per tertile increment in caregiver depression. Higher caregiver social support was associated with lower distress and higher positive outlook ( β  = 3%; 95%CI:1.4%, 4.5%) in their children. HIV‐infected/exposed children had most caregiver depression‐related QOL deficit ( β  = −5.2%/−6.8%; 95%CI: −12.4%, −0.2%) and HIV‐unexposed children had most caregiver social support‐related enhancements in positive outlook ( β =4.5%; 95%CI:1.9%, 7.1%). Conclusions: Caregiver anxiety, depressive symptoms and low social support were associated with worse well‐being in school‐aged and adolescent children. Improvement of caregiver mental health and strengthening caregiver social support systems may be a viable strategy for improving well‐being of vulnerable children and adolescents in this setting.